2015
DOI: 10.1007/s00442-015-3381-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental fertilization increases amino acid content in floral nectar, fruit set and degree of selfing in the orchid Gymnadenia conopsea

Abstract: Floral traits have evolved to maximize reproductive success by attracting pollinators and facilitating pollination. Highly attractive floral traits may, however, also increase the degree of self-pollination, which could become detrimental for plant fitness through inbreeding depression. Floral nectar is a trait that is known to strongly mediate pollinator attraction and plant reproductive success, but the particular role of the nectar amino acid (AA) composition is poorly understood. Therefore, we experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…For instance, Hoover et al . [13] showed that bumblebees were more attracted to a nectar solution mimicking nectar of plants under nitrogen fertilization, despite a twenty percent reduction in survival rate of individual workers compared to workers fed by control nectar solutions. Therefore, elucidating the precise effect of amino acid and sugar composition of pollen and nectar on pollinator health and fitness merits further research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Hoover et al . [13] showed that bumblebees were more attracted to a nectar solution mimicking nectar of plants under nitrogen fertilization, despite a twenty percent reduction in survival rate of individual workers compared to workers fed by control nectar solutions. Therefore, elucidating the precise effect of amino acid and sugar composition of pollen and nectar on pollinator health and fitness merits further research.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results are in line with the results of Hoover et al . [13], who found a higher mortality of bumblebee workers feeding on a controlled synthetic amino acid and sugar solution mimicking that of fertilized plants, free from the possible confounding effects of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations